Idiomatic Expression in Poetry as Authentic Materials for Teaching English at Senior High Schools - Ramadhani, Amalia Rizki; Safriani, Afida; Asmiyah, Siti (Department of English Language Education, UIN Sunan Ampel Surabaya, 2025)
Idioms are a component of a word group or a sentence that incorporates two or more words with a meaning that contrasts with their literal meaning. Additionally, idioms are an excellent way to enhance sentences. This study examines types of idiomatic expressions in Emily Dickinson's Selected Poems and their relevance to K-13 basic competence for High School eleventh grade. This study employed qualitative research to examine types of idiomatic expressions in Emily Dickinson’s “Emily Dickinson Selected Poems” using checklist tables as an instrument. The findings revealed that there are 45 Dickinson poems, focusing on life, love, nature, special abilities, and friendship, and identified five poems containing idiomatic expressions. These expressions can be authentic materials for English Language Teaching in Indonesian high schools. This study concludes that Dickinson’s book is authentic material for teaching English in senior high schools. The researcher suggests using the findings for teaching English in senior high schools, improving students’ understanding of idiomatic expressions, and analyzing idiomatic expressions in other authentic materials.